Recovery from temporary endoplasmic reticulum stress in plants relies on the tissue‐specific and largely independent roles of bZIP28 and bZIP60, as well as an antagonizing function of BAX‐Inhibitor 1 upon the pro‐adaptive signaling mediated by bZIP28. (2nd December 2017) - Ruberti, Cristina; Lai, YaShiuan; Brandizzi, Federica
Summary: The unfolded protein response (UPR) is an ancient signaling pathway that commits to life‐or‐death outcomes in response to proteotoxic stress in the endoplasmic reticulum (ER). In plants, the membrane‐tethered transcription factor bZIP28 and the ribonuclease‐kinase IRE1 along with its splicing target, bZIP60, govern the two cytoprotective UPR signaling pathways known to date. The conserved ER membrane‐associated BAX inhibitor 1 (BI1) modulates ER stress‐induced programmed cell death through yet‐unknown mechanisms. Despite the significance of the UPR for cell homeostasis, in plants the regulatory circuitry underlying ER stress resolution is still largely unmapped. To gain insights into the coordination of plant UPR strategies, we analyzed the functional relationship of the UPR modulators through the analysis of single and higher order mutants of IRE1, bZIP60, bZIP28 and BI1 in experimental conditions causing either temporary or chronic ER stress. We established a functional duality of bZIP28 and bZIP60, as they exert partially independent tissue‐specific roles in recovery from ER stress, but redundantly actuate survival strategies in chronic ER stress. We also discovered that BI1 attenuates the pro‐survival function of bZIP28 in ER stress resolution and, differently to animal cells, it does not temper the ribonuclease activity of inositol‐requiring enzyme 1 (IRE1) under temporary ER stress. Together these findings reveal a functional independence of bZIP28 and bZIP60 in plant UPR, and identify an antagonizing role of BI1 in the pro‐adaptive signaling mediated by bZIP28, bringing to light the distinctive complexity of the unfolded protein response (UPR) in plants. Significance Statement: Increased protein secretion activates the UPR to facilitate protein folding and quality control, or ignite apoptosis. Insufficient UPR causes human diseases and sub‐optimal crop yields. Yet‐unknown mechanisms link plant UPR signaling strategies. Here, we have mapped so far unpredicted steps in the circuitry management of plant UPR, which support conservation and divergence of stress management in eukaryotes.